Sociocultural Power of Biblical Translation in Early Modern Europe: The Cases of the Ostroh Bible (1581) and the King James Bible (1611) - Shmiher, Taras; Dzera, Oksana (Verbum Vitae, 2023)
This paper presents sociocultural profiles of the Ostroh Bible (1581) and the King James Version of the Bible (1611) in terms of their agency, authoritative status and regulative functions. Despite scholarly and popular attention given to both texts, no attempts have been made so far to compare them. This paper intends to break the mold and focuses on the causes and results of the collective agency of the two versions at the textual, paratextual and extratextual levels as well as on the gatekeeping role of these translations and the ways they affected the development of their respective cultures. It is also demonstrated that the OB and the KJV performed the function of “the second originals.” Also subject to analysis are the prefaces to the two editions, which disclose information about important translation figures and deal with issues of universal and sacred history.